2018
DOI: 10.1111/jocd.12670
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of 5‐aminolevulinic acid 5% thermosetting gel photodynamic therapy (PDT) in the treatment of mild‐to‐moderate acne vulgaris. A two‐center, prospective assessor‐blinded, proof‐of‐concept study

Abstract: This proof-of-concept study supports the efficacy of 5% ALA thermosetting gel red-light PDT in inflammatory acne of the face with a relevant clinical improvement of inflammatory lesions with a very good tolerability profile. Clinical improvement was maintained in the medium term (Trial Registration Number: ISRCTN66066651).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…35 patients were examined. The results of the study confirmed the effectiveness of this method despite the reduction of ALA concentration (97). Figure 11)…”
Section: Pdd and Pdt In Italy ñ Clinical Trials (supporting
confidence: 65%
“…35 patients were examined. The results of the study confirmed the effectiveness of this method despite the reduction of ALA concentration (97). Figure 11)…”
Section: Pdd and Pdt In Italy ñ Clinical Trials (supporting
confidence: 65%
“…Depending on the wavelength, lasers act at different levels 32,33 ; in particular the infrared rays act on the sebaceous gland causing a thermal coagulation and consequently a reduced sebum production. 30 These include herbium glass and YAG laser. Other lasers that are used in acne are the diode laser and the pulse dye.…”
Section: Lasermentioning
confidence: 99%
“…Its efficacy in the treatment of acne has been shown by several studies 28,29 . A two‐center, prospective assessor‐blinded, proof‐of‐concept study assessed the effectiveness of PDT with red light in combination with 5% gel aminolevulinic acid in the treatment of the inflammatory component of mild‐to‐moderate acne 30 . Thirty‐five patients with moderate acne were enrolled and clinical status was assessed considering Global Acne Grade System (GAG) at baseline and after three sessions of PDT (each of 15 minutes) with a statistically significant reduction of GAG score ( P = .0001) 30 …”
Section: Treatment Of Mild‐to‐moderate Acnementioning
confidence: 99%
See 1 more Smart Citation
“…According to PDT in the treatment of mild‐to‐moderate acne vulgaris, 2 a 5.0% ALA solution was freshly prepared with ALA powder (Shanghai Fudan‐Zhangjiang BioPharmaceutical, Shanghai, China) in a dark room. Before the therapy was started, the patient's scalp was cleaned with iodine, and we used sterile disposable needles to remove the crust of the lesions.…”
Section: Case Reportmentioning
confidence: 99%